Discrepant ratios of arterial vs. venous thrombosis in hemophilias A and B as compared to FVII deficiency1. (24th May 2013) - Girolami, Antonio; Berti de Marinis, Giulia; Bertozzi, Irene; Peroni, Edoardo; Tasinato, Valentina; Lombardi, Anna Maria
Abstract Background The occurrence of a thrombotic event in congenital bleeding disorders has drawn considerable attention in recent years. Both patients with hemophilia and patients with von Willebrand disease and even those with rare coagulation disorders have been shown to present occasional thrombotic events. Little is known on the comparative prevalence of arterial vs. venous thrombosis in these patients. Objectives The purpose of the present investigation was to evaluate the prevalence of arterial vs. venous occlusions in hemophilia A and B vs. FVII deficiency. Methods A time unlimited search of the literature was carried out using pertinent key words. Arterial or venous occlusions had to be proven by objective methods. Results Eighty‐five patients with hemophilia A or B have been reported to have had an arterial occlusion vs. six cases of FVII deficiency. On the contrary, 34 patients with hemophilia A or B and 32 cases with FVII deficiency have been reported to have presented with a venous thrombosis. The ratios of arterial vs. venous thrombosis are 3.72, 1.13, and 2.50 for hemophilia A, hemophilia B, and hemophilia A + B combined, respectively, and 0.19 for FVII deficiency. Conclusions Hemophilia A and hemophilia B do not protect from arterial occlusions (mainly acute coronary syndromes), whereas they assure some protection from venous thrombosis. The opposite seems true for FVII deficiency. The potential significance of this discrepancy is discussed.